Effects of the Fuel Price Increase on the Operating Cost of Freight Transport Vehicles - Gohari, A. (EDP Sciences, 2018)
One of the most important criteria in freight modal choices is the transport operating cost in which fuel price changes has a significant effect on it. This paper presents the impact of fuel price increases on the operating cost of the different transport modes for the containerized freight transportation. In this study, an operating cost equation was applied to compare the operating cost of different freight transport vehicles as well as evaluation of the operating cost changes across a range of fuel prices between the current price and one-hundred percent increase. The equation consists of influential parameters such as fuel cost, driver wage and maintenance cost of a vehicle. It has been concluded that the effect of the fuel price increase on the operating cost of different freight transportation modes is not in the same rate. According to equation and effective parameters considered, comparing the results showed that truck has the highest cost, train has the largest increase in price. Finally, the ship is the most influenced vehicle in terms of operating cost percentage increase when the rate of fuel price increase, followed by train and truck. Â© The Authors, published by EDP Sciences, 2018.